IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH ROLE PLAY TECHNIQUE OF VIII-D STUDENTS AT SMP WAHID HASYIM MALANG - SWANDAYANI, NURZAFIRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Speaking Ability, Role Play TechniqueSince communication is an essential need for human being, learning language takes place as a bridge to interact with others. Reflecting to the phenomenon, speakingcability is the most frequently used to communicate.  As an international language, the ability to speak English is needed especially for students to prepare for their future. However, the teaching of speaking in the classroom is still using the traditional approach such as read aloud in front of the class and repetitive drills. Based on the preliminary study that was conducted at SMP Wahid Hasyim Malang, especially in VIII-D class, most of students still found some difficulties in pronunciation, grammar, vocabulary, and confidence. Thus, the researcher proposed role play technique to improve students’ speaking ability of VIII-D students at SMP Wahid Hasyim Malang.This research used Classroom Action Research to cope with the students’ problem related to the speaking ability. Through role play technique, the students are able to express their ideas, feelings, and thoughts in a particular role. Besides, some instruments were also used in this research to support the data collection which was conducted in two cycles. Those instruments were observation checklist, interview, test, questionnaire, and field notes.From the result of this research, it was concluded that role play technique helped the students to cope with the speaking problem in English. It was supported by the accomplishment of the criteria of success The improvement of the students’ speaking ability also was seen from the final score in each post-test, in cycle I the final score was 38% of the students could pass the standard minimum score, while in cycle II the final score was 71% of the students could pass the standard minimum score. Meanwhile, it was also found from the questionnaire that 71% of the students felt motivated enough, while 29% of the students felt very motivated to learn English after being taught by using role play technique.